Pemanfaatan Lilin Biasa Menjadi Produk Lilin Aromaterapi Fresh Yang Bernilai Jual - Andi Mutiara Azzahra; Rahmadina Rahmadina; Alhafidz Asir; Muh Arifal; Sapar Sapar; Samsinar Samsinar (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The large population and density often cause stress for residents who live in urban areas, so they need to be relaxed so that their spiritual life is balanced. One method of relaxation that is often tried is by staying silent in a room filled with aromatherapy. Aromatherapy candles are an alternative to applying aromatherapy by inhalation or inhalation and can produce a refreshing aroma. Aromatherapy candles have many benefits, especially for people who are very busy. The purpose of the researchers to make this article is to provide information to the public that aromatherapy candles have benefits as refreshing and relaxing, as well as to inspire people to start their own businesses by turning ordinary candles into aromatherapy candles that are worth selling. The result of this dedication is aromatherapy candles which are refreshing because they are combined with essential oils to produce aroma. Through this community service, it is hoped that the community and students can use candles as a source of lighting as well as air freshener.